Insecticide residues in tuber crops and its effect on soil microbes - E.R. Harish; M. Afeefa; B.G. Sangeetha (JOURNAL OF ROOT CROPS, 2024)
Sucking pests are one of the most important problems in tuber crop cultivation. For the management of sucking pests’ whitefly, mealybug, scale etc., systemic insecticides like imidacloprid and dimethoate are recommended for drenching and spraying. In the present study, these insecticides were tested for their impact on soil micro-organisms and for their presence in cassava.Beneficial soil microbes Bacillus cereus, Beauveria bassiana and Trichoderma spp. were isolated from rhizosphere soil of tuber crops and their growth in insecticide applied media were compared. Residue analysis of the plant samples (cassava leaves and tubers) was conducted after the application of insecticides at recommended doses to the plants. Observations were taken after 1, 7, 14 and 30 days of application. From the LC-MS and GC-MS study, it was found that tuber (edible part) is safe from imidacloprid residue even 24 h after the application. But, 0.051 ppm dimethoate residue was noticed in cassava tubers after 30 days of drenching with the insecticide.